2015
DOI: 10.1123/jsr.2013-0073
|View full text |Cite
|
Sign up to set email alerts
|

Forearm Position’s Alteration of Radial-Head Impingement on Wrist-Extensor Tendons

Abstract: The authors recommend that the effect of radial-head position and its relationship to the area of tendon pathology be considered clinically in the rehabilitation of patients suffering from lateral epicondylalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Erak, Day and Wand [30] demonstrated a biomechanical basis for the involvement of the superficial head of supinator in the aetiology of lateral epicondylitis, whilst Stroyan and Wilk [31] suggested that supinator has a role in the stability of the radio-humeral and superior radio-ulnar joints particularly with tasks in pronation, such as gripping and lifting. More recently Ranger et al [32] suggested that the radial head may act as a cam in pronation, mitigating the load on the origin of extensor carpi radialis brevis (ECRB), all of which certainly require consideration clinically. In Phase three all 56 patients received strengthening exercises, 55 of which were commenced on the standardised isometric loading programme.…”
Section: Discussionmentioning
confidence: 99%
“…Erak, Day and Wand [30] demonstrated a biomechanical basis for the involvement of the superficial head of supinator in the aetiology of lateral epicondylitis, whilst Stroyan and Wilk [31] suggested that supinator has a role in the stability of the radio-humeral and superior radio-ulnar joints particularly with tasks in pronation, such as gripping and lifting. More recently Ranger et al [32] suggested that the radial head may act as a cam in pronation, mitigating the load on the origin of extensor carpi radialis brevis (ECRB), all of which certainly require consideration clinically. In Phase three all 56 patients received strengthening exercises, 55 of which were commenced on the standardised isometric loading programme.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic tendinopathy, the range of motion into end-range wrist flexion and pronation may be limited at the start of exercise training due to possible local compression effects 95 , 96 , 97 , 98 .…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…Bei der chronischen Tendinopathie kann das Bewegungsausmaß in die endgradige Handgelenkflexion und Pronation zu Beginn der Trainingstherapie aufgrund möglicher lokaler Kompressionseffekte limitiert werden 95 , 96 , 97 , 98 .…”
Section: Konservative Therapieunclassified
“…Exercises should also address motor control impairments, 23,85 such as dissociation of wrist from finger extension (FIGURE 5) and retraining of wrist alignment during gripping. Concentric and/or eccentric exercise of the wrist extensors is advocated for patients with degenerative-stage tendinopathy, 21 commencing with the elbow in flexion and restricting end-of-range wrist flexion, when the ECRB tendon may be exposed to greater compression and more pain 33,90 (FIGURE 6). A similar approach restricting full ankle dorsiflexion during eccentric exercises was more successful for patients with insertional Achilles tendi-exercise has been shown to lead to greater and faster regression of pain, 83 less sick leave, fewer medical consultations, and increased work ability.…”
mentioning
confidence: 99%